An Attempt to Accord the Quality of Therapy of Stable Coronary Heart Disease Patients with Current Clinical Guidelines (ALIGN study): Design and the First Results - S. Yu. Martsevich; E. D. Zharkova; N. P. Kutishenko; Yu. V. Lukina; S. N. Tolpygina; V. P. Voronina; A. V. Zagrebelnyy (Рациональная фармакотерапия в кардиологии, 2020)
Aim. To assess the quality of therapy in stable coronary heart disease (CHD) patients, who first sought consultation in the specialized cardiology department of the research center, and try to adjust the therapy in accordance with current clinical guidelines, paying special attention to achieving the target levels of blood pressure, low-density lipoprotein cholesterol (LDL), and glycosylated hemoglobin (in patients with diabetes mellitus), increasing exercise tolerance and improving the quality of life (QL).Material and methods. The ALIGN study is an integral part of the PROFILE outpatient registry. ALIGN study included all patients with verified coronary heart disease who came for consultation to the specialized institution for the first time or for the first time in more than the last 3 years. Patients have been recruited from December 01, 2017 to December 31, 2019. The study consisted of 4 visits: the first-time visit – inclusion in the study (V0), when drug therapy, QL, and adherence were evaluated, and therapy correction was made in accordance with clinical guidelines. In 3 months (V1) the target values of clinical and laboratory parameters were estimated. The third visit (V2) was planned to take place 1 year after the first visit with reevaluation of QL and patients' adherence to treatment, and effectiveness of the therapy. The fourth visit (V3)/telephone contact was planned in 2 years after the first visit to assess life status, get information about complications and therapy.Results. 389 people were included in the PROFILE registry for the specified period of time, 79 had a verified diagnosis of CHD, and 71 patients were included in the ALIGN study: 55 men (aged of 68.7±8.96 years) and 16 women (aged of 67.5±8.08 years). Arterial hypertension was registered in 90.1% of patients, stable angina class I-III – in 62%, 47.9% of patients had a history of acute myocardial infarction (AMI), 52.1% had percutaneous coronary intervention, 15.5% of patients had coronary artery bypass graft, chronic heart failure was detected in 40.8%, diabetes mellitus – in 21.1%, atrial fibrillation – in 15.5% of patients. Lipid-lowering drugs were taken by 53 (74.6%) patients, but only 21 (29.6%) achieved the target values of LDL cholesterol. Angiotensin-converting enzyme inhibitors were taken by 34 patients (47.9%), and angiotensin receptor blockers by 15 (21%) of patients, 47 (66.2%) patients took beta-blockers, antiplatelet agents were taken by 61 people, and anticoagulants by 10 patients. Patients who had a history of AMI had been prescribed BB in 88%, statins – in 90%, and renin-angiotensin-aldosterone system (RAAS) blockers – in 80% of cases.Conclusions. Initial quality of therapy for patients with stable CHD did not fully match the clinical guidelines: a quarter of patients did not receive lipidlowering therapy, and target levels of LDL cholesterol were achieved only in one third of patients. Among patients who had a history of AMI, every fifth patient did not receive RAAS blockers.